Evaluation of Temperature, DO and BOD in Mosul Dam Lake Using Geographical Information System - Aljoborey, Abdulmunem Dherar Abdullah; Abdulhay , Hind Suhail (Iraqi Journal of Science, 2020)
The aim of this study is to evaluate the seasonal variations of Mosul dam lake by measuring the temperature, dissolved oxygen (DO) and biochemical oxygen demand (BOD) during the period from July 2018 to April 2019. Twenty two sites were selected within the studied lake. The obtained results were integrated with the geographical information system (GIS) using spatial images to create maps utilizing Arc map software. These maps were used to demonstrate the concentrations of the investigated parameters during the study period. The results show that all parameters were within the accepted levels, indicating the good status of the lake.